NaHCO₃-Assisted Synthesis of Ni-Promoted Sulfated Mesoporous Silica for the Hydrocracking of Used Cooking Oil into Biogasoline - Karna Wijaya; Marini Fairuz Vebryana; Niko Prasetyo; Aldino Javier Saviola; Wahyu Dita Saputri; Amalia Kurnia Amin; Latifah Hauli; Saharman Gea (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Biofuel production from biomass sources remains a key area of research, aimed at reducing reliance on fossil fuels and promoting environmental sustainability. This study investigates the conversion of used cooking oil (UCO) into biogasoline via catalytic hydrocracking, employing sulfated mesoporous silica dispersed with nickel as the catalyst. Mesoporous silica was synthesized using tetraethyl orthosilicate (TEOS) and NaHCO₃ as the template, followed by a hydrothermal method to introduce sulfate groups and nickel metal. Among the synthesized catalysts, SMS-2 exhibited the highest acidity across varying sulfuric acid concentrations, while 1 Ni/SMS-2 demonstrated superior acidity compared to other nickel loadings. The SiO₂, SMS-2, and 1 Ni/SMS-2 catalysts were evaluated for UCO hydrocracking in a semi-batch double-furnace reactor operated at an optimum temperature of 550 °C for 2 h, with a hydrogen flow rate of 20 mL min⁻¹ under atmospheric pressure. Modifying mesoporous silica with sulfuric acid and nickel significantly enhanced its catalytic performance, with the 1 Ni/SMS-2 catalyst achieving the highest liquid product yield (66.10%) and gasoline fraction (35.47%) at an optimum catalyst-to-feed ratio of 1:100 (w/w). Notably, the resulting biogasoline exhibited a calorific value comparable to commercial gasoline and was free of aromatic hydrocarbons, indicating the potential for cleaner combustion. This study provides valuable insights into the effectiveness of mesoporous silica-based catalysts, highlighting their acid site modulation capabilities for efficiently transforming waste into high-value fuels. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).